The effect of treatment response on endothelial function and arterial stiffness in depression. A prospective study. - Kokras, Nikolaos; Papadopoulou, Efthymia; Georgiopoulos, Georgios; Dalla, Christina; Petropoulos, Ioannis; Kontogiannis, Christos; Laina, Ageliki; Bampatsias, Dimitrios; Stellos, Konstantinos; Kouzoupis, Anastasios V; Stamatelopoulos, Kimon (J Affect Disord, 2019)
BACKGROUND: Major depression is associated with endothelial dysfunction and arterial stiffening, which may mediate development of hypertension and increased cardiovascular risk. The effect of response to antidepressant treatment on these vascular parameters has not been elucidated. AIMS: We aimed to assess the net effect of antidepressant therapy on endothelial function and arterial stiffness in patients with psychotic depression. METHOD: Thirty-seven patients with major psychotic depression, according to DSM-IV-TR, were treated with titrated citalopram 20-60 mg and risperidone 0.5-1 mg and were followed for 6 months. Twelve additional patients who denied treatment, or were non-compliant, were also followed for the same time period. Vascular function was assessed by flow-mediated dilatation (FMD), carotid-femoral pulse wave velocity (PWV) and augmentation index (AI), at baseline and at the end of follow-up. RESULTS: Aortic and peripheral blood pressure (BP), PWV, FMD and AI (p < 0.05 for all) were significantly improved in the group that received treatment. Overall, only responders to treatment (n = 24) presented significant improvements in all hemodynamic and vascular parameters (p < 0.05 for all), irrespectively of traditional cardiovascular risk factors (TRFs), vasoactive medication and BP lowering. In a secondary analysis, patients with psychotic depression presented worse endothelial function as compared to controls matched for TRFs. LIMITATIONS: Non-randomized study. CONCLUSIONS: Patients who respond to therapy for major psychotic depression present sustained improvement in vascular function. Given that depressed patients are considered to be at high cardiovascular risk and are often non-compliant with treatment, further research to assess cardiovascular benefits of vigilant monitoring of antidepressant therapy is warranted.
Keywords: Adult; Antidepressive Agents; Blood Pressure; Citalopram; Depressive Disorder; Endothelium, Vascular; Female; Hemodynamics; Humans; Hypertension; Male; Middle Aged; Prospective Studies; Pulse Wave Analysis; Vascular Stiffness